Similarity Analysis of the Default Transition of Bond Issuer in Indonesia using Euclidean Distance - Aulia Ikhsan; Fikri C Permana; Ayu Nurulhaq Putri; Rifki Hamdani; Mukhtar Mukhtar; Syarif Abdullah; Rifqy Hafizh; Muhammad Hikam Adiguna; Dinda Dwi Anugrah Pertiwi; Kinanthi Trah Asmaraningtyas (Theta: Journal of Statistics, 2025)
The debt instrument (bond) as one of the investment instruments in the Capital Market has a main risk known as default. Default risk can be mitigated if investors assess the credit quality of the bond and its issuer, as measured by rating. In this research, the initial rating of issuers was investment grade (BBB or higher) and valid for at least 1 year, with their business operations based in Indonesia. The observation period was from 2007 to 2023. A Markov Chain was used to create a transition matrix to analyze transitions and default. The probability of AAA staying over 1 year is 0.9858 whereas the likelihood of AA, A, and BBB staying in the same rating is 0.9203, 0.8825, and 0.8630, respectively. The BBB in a 5-year transition has the highest probability of default by 0.0370. The Euclidean distance was used to measure the similarity of default durations. The 1-year and 3-year transition have the shortest distance, at  0.00939. The conclusion of this research is a higher rating has a higher probability of staying at the same rating and carries lower risk. Furthermore, 1-year and 3-year transitions show similarities based on their probability of default.